Promising potential of articaine-loaded poly(epsilon-caprolactone) nanocapules for intraoral topical anesthesia - Silva, Camila Batista da; Volpato, Maria Cristina; Muniz, Bruno Vilela; Santos, Cleiton Pita dos; Serpe, Luciano; Nunes Ferreira, Luiz Eduardo; Silva de Melo, Nathalie Ferreira [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Groppo, Francisco Carlos; Franz-Montan, Michelle (Public Library Science, 2021)
To determine whether the permeation capacity and analgesic efficacy of articaine (ATC) could be increased and cytotoxicity decreased by encapsulation in poly(e-caprolactone) nanocapsules (ATC(nano)), aiming at local or topical anesthesia in dentistry. Cellular viability was evaluated (using the MTT test and fluorescence microscopy) after 1 h and 24 h exposure of HaCaT cells to ATC, ATC(nano), ATC with epinephrine (ATC(epi)), and ATC in nanocapsules with epinephrine (ATC(nanoepi)). The profiles of permeation of 2% ATC and 2% ATC(nano) across swine esophageal epithelium were determined using Franz-type vertical diffusion cells. Analgesic efficacy was evaluated with a von Frey anesthesiometer in a postoperative pain model in rats, comparing the 2% ATC, 2% ATC(nano), 2% ATC(epi), and 2% ATC(nanoepi) formulations to 4% ATC(epi) (a commercially available formulation). We show that use of the nanocapsules decreased the toxicity of articaine (P<0.0001) and increased its flux (P = 0.0007). The 2% ATC(epi) and 4% ATC(epi) formulations provided higher analgesia success and duration (P<0.05), compared to 2% ATC, 2% ATC(nano), and 2% ATC(nanoepi). Articaine-loaded poly(e-caprolactone) nanocapsules constitute a promising formulation for intraoral topical anesthesia (prior to local anesthetic injection), although it is not effective when injected in inflamed tissues for pain control, such as irreversible pulpitis.